Development of Slowly Digestible Starch Derived α-Glucans with 4,6-α-Glucanotransferase and Branching Sucrase Enzymes - te Poele, E. M. (J Agric Food Chem, 2020)
[Image: see text] Previously, we have identified and characterized 4,6-α-glucanotransferase enzymes of the glycosyl hydrolase (GH) family 70 (GH70) that cleave (α1→4)-linkages in amylose and introduce (α1→6)-linkages in linear chains. The 4,6-α-glucanotransferase of Lactobacillus reuteri 121, for instance, converts amylose into an isomalto/malto-polysaccharide (IMMP) with 90% (α1→6)-linkages. Over the years, also, branching sucrase enzymes belonging to GH70 have been characterized. These enzymes use sucrose as a donor substrate to glucosylate dextran as an acceptor substrate, introducing single -(1→2,6)-α-d-Glcp-(1→6)- (Leuconostoc citreum enzyme) or -(1→3,6)-α-d-Glcp-(1→6)-branches (Leuconostoc citreum, Leuconostoc fallax, Lactobacillus kunkeei enzymes). In this work, we observed that the catalytic domain 2 of the L. kunkeei branching sucrase used not only dextran but also IMMP as the acceptor substrate, introducing -(1→3,6)-α-d-Glcp-(1→6)-branches. The products obtained have been structurally characterized in detail, revealing the addition of single (α1→3)-linked glucose units to IMMP (resulting in a comb-like structure). The in vitro digestibility of the various α-glucans was estimated with the glucose generation rate (GGR) assay that uses rat intestinal acetone powder to simulate the digestive enzymes in the upper intestine. Raw wheat starch is known to be a slowly digestible carbohydrate in mammals and was used as a benchmark control. Compared to raw wheat starch, IMMP and dextran showed reduced digestibility, with partially digestible and indigestible portions. Interestingly, the digestibility of the branching sucrase modified IMMP and dextran products considerably decreased with increasing percentages of (α1→3)-linkages present. The treatment of amylose with 4,6-α-glucanotransferase and branching sucrase/sucrose thus allowed for the synthesis of amylose/starch derived α-glucans with markedly reduced digestibility. These starch derived α-glucans may find applications in the food industry.